Pengaruh Edukasi Media Video Animasi terhadap Pengetahuan Personal Hygiene Menstruasi pada Siswi di SMP Tunas Harapan Kabupaten Bogor Tahun 2024 - Hana Luthfiana Lathifah; Nurul Ainul Shifa; Bambang Suryadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Maintaining personal hygiene during menstruation is crucial to prevent infections in the reproductive system. Many young women still have limited knowledge regarding proper hygiene practices during menstruation. This lack of awareness can lead to health issues, such as infections in the reproductive tract and other complications. An effective educational approach is needed to enhance the understanding of young women, one of which could be through animated video content. Animated videos as an educational tool have the advantage of delivering information in a visually engaging, simple, and easy-to-understand manner, making them more effective in improving knowledge about personal hygiene during menstruation. This study aims to assess the impact of animated video education on female students' knowledge of personal hygiene during menstruation. The research follows a quantitative approach with a One Group Pre-Test and Post-Test pre-experimental design. The study sample consisted of 32 seventh-grade female students, selected through the total sampling technique. Data analysis included both univariate and bivariate analysis. For bivariate analysis, a normality test was performed using the Wilcoxon test with a significance level (α) ≤ 0.05. The study results showed a p-value of 0.000 (p < 0.05), indicating a significant effect of animated video education on the knowledge of personal menstrual hygiene among female students.